2015
DOI: 10.21446/scg_ufrj.v9i2.13319
|View full text |Cite
|
Sign up to set email alerts
|

Contrato Psicológico em Empresas de Alta Performance: A Dor e a Delícia de ser um Trabalhador Contemporâneo

Abstract: Mudanças mais amplas na estrutura produtiva capitalista delinearam um cenário marcado pela competição acirrada entre as empresas, que vem demandando uma mão de obra cada vez mais comprometida e disposta a dedicar grande parte de seu tempo às organizações (GREEN, 2001). Esta dedicação intensa do trabalhador envolve aspectos que vão desde o aumento das horas de trabalho, passando pela forma de pensar na organização, vista como uma extensão da própria vida, até a opção pelo trabalho, em detrimento da vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…In Brazil, the idea of loving one’ job is disseminated in popular management literature and in the business media, but still has limited coverage in academic journals. Nevertheless, Neves et al (2014) revealed that qualified professionals often attempt to justify the heavy workload to which they are submitted on a daily basis, by arguing that they do it because they ‘ love their jobs’. Such a rationalisation of the intensification of work draws our attention to the reproduction of socially accepted discourses to justify such a condition.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the idea of loving one’ job is disseminated in popular management literature and in the business media, but still has limited coverage in academic journals. Nevertheless, Neves et al (2014) revealed that qualified professionals often attempt to justify the heavy workload to which they are submitted on a daily basis, by arguing that they do it because they ‘ love their jobs’. Such a rationalisation of the intensification of work draws our attention to the reproduction of socially accepted discourses to justify such a condition.…”
Section: Introductionmentioning
confidence: 99%
“…Embora a literatura identifique consequências nocivas decorrentes do trabalho intensificado, outras pesquisas apontam para fatores de manutenção dos trabalhadores sob essas condições, tais como o sentimento de recompensa pelos desafios, aprendizado, oportunidades de carreira, status e salários recebidos em contrapartida, além do medo e da insegurança com relação ao futuro (Burke & Fiksenbaum, 2008;Neves, Lemos, & Costa, 2014).…”
unclassified